Projected Outcomes of Nurse-Family Partnership Home Visitation During 1996–2013, USA - Miller, Ted (Springer, 2015)
Nurse-Family Partnership (NFP) targets intensive prenatal and postnatal home visitation by registered nurses to low-income first-time mothers. Through 2013, 177,517 pregnant women enrolled in NFP programs. This article projects how NFP will affect their lives and the lives of their babies. NFP has been evaluated in six randomized trials and several more limited analyses of operational programs. We systematically reviewed evaluation findings on 21 outcomes and calculated effects on three more. We added outcome data from the NFP national data system and personal communications that filled outcome data gaps on some trials. We assumed effectiveness in replication declined by 21.8 %, proportionally with the decline in mean visits per family from trials to operational programs. By 2031, NFP program enrollments in 1996–2013 will prevent an estimated 500 infant deaths, 10,000 preterm births, 13,000 dangerous closely spaced second births, 4700 abortions, 42,000 child maltreatment incidents, 36,000 intimate partner violence incidents, 90,000 violent crimes by youth, 594,000 property and public order crimes (e.g., vandalism, loitering) by youth, 36,000 youth arrests, and 41,000 person-years of youth substance abuse. They will reduce smoking during pregnancy, pregnancy complications, childhood injuries, and use of subsidized child care; improve language development; increase breast-feeding; and raise compliance with immunization schedules. They will eliminate the need for 4.8 million person-months of child Medicaid spending and reduce estimated spending on Medicaid, TANF, and food stamps by $3.0 billion (present values in 2010 dollars). By comparison, NFP cost roughly $1.6 billion. Thus, NFP appears to be a sound investment. It saves money while enriching the lives of participating low-income mothers and their offspring and benefiting society more broadly by reducing crime and safety net demand.